Trading places [videorecording (DVD)] - Landis, John, 1950-; Aykroyd, Dan; Murphy, Eddie, 1961-; Bellamy, Ralph, 1904-1991; Ameche, Don; Elliott, Denholm; Curtis, Jamie Lee, 1958- (Paramount Home Entertainment, 2007)
Two old business partners bet that they can turn a street hustler into a successful businessman.